Diphosphonate cavitands as molecular cups for l-lactic acid. Issue 26 (9th March 2016) - Barboza, T.; Pinalli, R.; Massera, C.; Dalcanale, E.
Abstract : Two isomeric diphosphonate cavitands (ABii andACii ) were probed for the molecular recognition ofl -lactic acid in solution via NMR spectroscopy and in the solid state via crystal structure determination. The interactions involved in the recognition event are a combination of hydrogen bonding and CH–π interactions. Abstract : The complexation ofl -lactic acid by two isomeric diphosphonate cavitands was studied, both in solution and in the solid state. 1 H and 31 P NMR experiments and X-ray diffraction analysis on single crystals evidenced the formation of a supramolecular host–guest adduct with both synthetic receptors, driven by a combination of H-bonding and C–H⋯π interactions.